Human developmental research : experience from research in Hong Kong - Shek, Daniel T. L. (Pediatrics, Child and Adolescent Health (Series Editor: Joav Merrick - National Institute of Child H., 2013)
Human development research commonly addresses the ""what"", ""when"", ""how"", ""why"", ""who"", and ""where"" of human development. For example, with reference to the development of resilience in adolescence, researchers often ask what are the components of resilience (""what""), their development at different time points (""when""), and the related trajectories (""how""). Researchers also attempt to understand factors influencing resilience (""why"") in different adolescents (""who"") in different cultures (""where""). In many adolescent research studies, researchers are interested in asking.